THE EFFECTS OF CADMIUM ON THE TESTES (Experimental biology, 2025)
Among toxic metals affecting the reproductive system, cadmium plays the most significant role. Cadmium is one of the factors that impair testicular function. The mechanisms of action of cadmium in the testes are very complex and include damage to the vascular endothelium of germ cells, Sertoli and Leydig cells, and intercellular adhesions. This metal enhances the action of free radicals, causes changes in enzyme systems and induces an inflammatory response. Morphologic changes induced by cadmium include interstitial edema and necrosis of seminal tubules. The aim of this article was to investigate the effects on the testes, to evaluate the subchronic effects on the testes. The adult male Wistar rats were divided into four groups for the purposes of this study: control group, second group that received a cadmium chloride solution at the maximum permissible concentration (0.001 mg/L), third group that received a sub-lethal dose of cadmium chloride (0.01 mg/L), and fourth group that received a shock dose (0.1 mg/L). The concentration of essential minerals and cadmium in the testicles was assessed, as well as the histology and histomorphometry of the testicles. An increase in the number of apoptotic cells was observed at subtoxic and shock doses. Furthermore, degenerative changes in the testicular epithelium, the death of germ cells, and damage to Leydig cells were observed. The results confirm that the severity of Cd-induced testicular damage depends on the route as well as the duration of exposure.
Keywords: cadmium, testes, toxicity, reproductive system, oxidative stress